(untitled) (Journal of actual problems of jurisprudence, 2021)
The article is devoted to the analysis of a separate category of administrative offenses that infringe on the rights of the individual under the legislation of the Republic of Kazakhstan, for which the decision to initiate a case is made by the prosecutor. The authors of the article consider the norms of the current legislation of the Republic of Kazakhstan regulating legal relations regarding the rights and freedoms of the individual, citizen, which according to the Code of Administrative Offenses of the Republic of Kazakhstan, Chapter 10 is devoted to administrative offenses that infringe on the rights of the individual. However, according to Article 805 of the Administrative Code of the Republic of Kazakhstan, “ The Prosecutor makes a decision on the initiation of cases of administrative offenses provided for in Articles 74, 75 76, 77, 78, 79, 81, 82, 82-1, 93, 94, 95, 96, 97, 98, 99, 100...”. The authors of the article characterize two elements of administrative offenses provided for in Articles 74 and 76 of the Code of Administrative Offenses of the Republic of Kazakhstan. Thus, Article 74 of the Code of Administrative Offences provides for the responsibility of officials for committing illegal actions (omissions) that prevent a person from obtaining citizenship of the Republic of Kazakhstan. Article 76 of the Code of Administrative Offences provides for liability for «the action (inaction) of officials that restricts the right of individuals to freedom of movement and choice of place of residence”. Key words: state, law, personality, administrative law, offense.